Type-II Core/Shell Nanowire Heterostructures and Their Photovoltaic Applications - Cao, Yiyan; Wu, Zhiming; Ni, Jianchao; Bhutto, Waseem. A.; Li, Jing; Li, Shuping; Huang, Kai; Kang, Junyong (Nano-Micro Letters, 2012)
Nanowire-based photovoltaic devices have the advantages over planar devices in light absorption and charge transport and collection. Recently, a new strategy relying on type-II band alignment has been proposed to facilitate efficient charge separation in core/shell nanowire solar cells. This paper reviews the type-II heterojunction solar cells based on core/shell nanowire arrays, and specifically focuses on the progress of theoretical design and fabrication of type-II ZnO/ZnSe core/shell nanowire-based solar cells. A strong photoresponse associated with the type-II interfacial transition exhibits a threshold of 1.6 eV, which demonstrates the feasibility and great potential for exploring all-inorganic versions of type-II heterojunction solar cells using wide bandgap semiconductors. Future prospects in this area are also outlooked.